The relationship between selected macroeconomic variables towards stock market in Malaysia / Nurdiyana Mohd Shah - Mohd Shah, Nurdiyana (Faculty of Business and Management, 2017)
The aim of this study is to investigate the relationship between macroeconomic variables which consist of inflation rate, interest rate and money supply towards the stock market in Malaysia represent by FTSE Bursa Malaysia KLCI Index. The study used Single Linear Regression and Multiple Linear Regression in order to find the relationship among independent variables and dependent variable. The data is collected from year 1985 until 2015 and conduct in yearly basis. From the result, it reveals that inflation rate has a negative insignificant relationship towards stock market (FTSE Bursa Malaysia KLCI). While interest rate and money supply have a positive insignificant relationship towards (FTSE Bursa Malaysia KLCI). These results give additional understanding of the relationship between the macroeconomic variables and FTSE Bursa Malaysia KLCI and should be useful for regulator, investor and speculator.